2016
DOI: 10.1542/peds.2015-3257
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sirolimus in the Treatment of Complicated Vascular Anomalies

Abstract: Sirolimus was efficacious and well tolerated in these study patients with complicated vascular anomalies. Clinical activity was reported in the majority of the disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
794
4
35

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 654 publications
(860 citation statements)
references
References 31 publications
(29 reference statements)
27
794
4
35
Order By: Relevance
“…Rapamycin has shown efficacy in clinical trials of lymphangiomatosis and other lymphatic anomalies (3,4,11,12). Rapamycin has also been used extensively in mice over a wide range of doses (29,30).…”
Section: Dose Response Of Rapamycinmentioning
confidence: 99%
See 3 more Smart Citations
“…Rapamycin has shown efficacy in clinical trials of lymphangiomatosis and other lymphatic anomalies (3,4,11,12). Rapamycin has also been used extensively in mice over a wide range of doses (29,30).…”
Section: Dose Response Of Rapamycinmentioning
confidence: 99%
“…Rapamycin and related mTORC1 inhibitors are being used with promising results in the treatment of lymphatic malformations (4,(80)(81)(82), which build on what is known from the treatment of patients with LAM (27,83). Favorable responses provide incentive for learning more about the actions of mTORC1 inhibitors in the treatment of lymphatic anomalies.…”
Section: Attributes and Limitations Of The Ccsp/vegf-c Mouse Model Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…Another study showed that Sirolimus is a well-tolerated. The common grade three side effects bone marrow toxicity in 27%, gastrointestinal toxicity in 3% and metabolic toxicity in 3% [74,75].…”
Section: Role Of Mtor Inhibitorsmentioning
confidence: 99%